Participatory Arts-based Game Design: Mela, a Serious Game to Address SGBV in Ethiopia - Sadati, S M Hani; Mitchell, Claudia (Loading, 2024)
The emerging body of work on participatory game design (PGD) highlights the significance of working with end-users’ voices as the starting point. This is particularly critical in serious games that seek to impact social change in areas such as sexual and gender-based violence (SGBV). This article, which is based on fieldwork with 16 college instructors in four agricultural colleges in rural Ethiopia, draws together concepts of participatory visual methods (particularly cellphilming), PGD and a game universe perspective to offer an engaging and interactive approach to the design of serious games. We refer to this as ‘Participatory Arts-based Game Design’ (PAGD), an approach that was used to create Mela, a serious game to address SGBV in Ethiopian agriculture colleges. Exploring Mela game’s participatory and engaging design process, this article offers a framework for serious game development to address critical social change issues that go beyond the game itself. It has the potential to not only place the end-users at the centre but to recognize the critical role of engagement and immersivity in a field oriented towards impact and sustainability.